âˆ†1-Pyrroline-5-carboxylate synthetase(P5CS) - Isolation, partial purification, and its characterization - Sharada, P; Naik, G R (Recent Research in Science and Technology, 2011)
âˆ†1-Pyrroline-5-carboxylate synthetase, the bi functional enzyme participating in proline biosynthetic pathway was isolated and partially purified from groundnut leaves. Following ammonium sulphate fractionation, purification was performed by several chromatographic methods: Sephadex G-75 and DEAE cellulose. The enzyme was resolved by anion exchange chromatography. The γ -GK activity was detected by the hydroxamate assay.The subunit molecular mass of P5CS was estimated to be 70KDa.Proline accumulation has been correlated with tolerance to drought stress in plants. P5CS is able to catalyze the conversion of glutamate to pyrrroline-5-carboxylate, which is then reduced to proline by pyrroline-5-reductase.